PERFORMANCE ASSESSMENT OF RICE VARIETY MCM 103 IN SALINE SOILS OF WEST GODAVARI DISTRICT THROUGH FRONTLINE DEMONSTRATIONS - PODAPATI , VINAYA LAKSHMI (The Journal of Research ANGRAU, 2026)
The study was undertaken by Krishi Vigyan Kendra, Undi as a Front Line Demonstration (FLD) on rice MCM 103 variety in five locations during Kharif for two consecutive years during 2023 & 2024, to assess the performance of rice variety MCM 103 on yield and economics of rice. The higher yield i.e., 5273, 5062 kg/ha was noticed with MCM 103 rice variety compared to MTU 7029 (4959 and 4875 kg/ha) during both the years of assessment. Net returns and B:C ratio were higher with MCM 103 rice variety (Rs. 46414, 44446 and 45430/ha and 2.16, 2.35 and 2.25) when compared to farmers practice (Rs. 37480, 39105 and 38293 /ha and 1.8, 2.01 and 1.90) during 2023, 2024 and in pooled data, respectively.